Fragmentation of interstellar methanol by collisions with He˙+: an experimental and computational study. Issue 37 (14th September 2022) - Richardson, Vincent; Valença Ferreira de Aragão, Emília; He, Xiao; Pirani, Fernando; Mancini, Luca; Faginas-Lago, Noelia; Rosi, Marzio; Martini, Luca Matteo; Ascenzi, Daniela
Abstract : A combined experimental and theoretical study demonstrates the presence of stereodynamical effects in the charge exchange reactivity of He˙ + with CH3 OH, a key process in the astrochemistry of methanol. Abstract : Methanol is a key species in astrochemistry as its presence and reactivity provides a primary route to the synthesis of more complex interstellar organic molecules (iCOMs) that may eventually be incorporated in newly formed planetary systems. In the interstellar medium, methanol is formed by hydrogenation of CO ices on grains, and its fate upon collisions with interstellar ions should be accounted for to correctly model iCOM abundances in objects at various stages of stellar evolution. The absolute cross sections (CSs) and branching ratios (BRs) for the collisions of He˙ + ions with CH3 OH are measured, as a function of the collision energy, using a Guided Ion Beam Mass Spectrometer (GIB-MS). Insights into the dissociative electron (charge) exchange mechanism have been obtained by computing the entrance and exit multidimensional Potential Energy Surfaces (PESs) and by modelling the non-adiabatic transitions using an improved Landau–Zener–Stückelberg approach. Notably, the dynamical treatment reproducing the experimental findings includes a strong orientation effect of the system formed by the small He˙ + ion and the highly polar CH3 OH molecule, in the electric field gradient associated to the strongly anisotropic intermolecular interaction. This is a stereodynamical effect that plays a fundamental role in collision events occurring under a variety of conditions, with kinetic energy confined within intervals ranging from the sub-thermal to the hyper-thermal regime.